A Rare Combination of Complex Congenital Heart Disease with Acquired Rheumatic Valvular Heart Disease - Chowdhury, Abdul Wadud; Haque, Azizul; Hosen, ABM Imam; Md Salim, Gias Uddin; Islam, Kazi Nazrul; Amin, Mohammod Gaffar; Hoque, Abu Taher Md Mahfuzul; Md Khalequzzaman, -; Hasan, Pratyay (Cardiovascular Journal, 2021)
Tetralogy of Fallot (TOF) is a complex cyanotic congenital heart disease with a survival beyond middle age. Rheumatic and congenital cyanotic heart disease are common causes of hospital admission. However, coexistence of rheumatic heart disease with complex congenital heart disease like TOF is known to occur very rarely. This report presents a case of rheumatic valvular heart disease (AR & MR) with a complex congenital heart disease (TOF with PDA with PLSVC) in a 30 yrs old female. Patient was treated by conservative management and advised for corrective surgery and double valve replacement. Cardiovasc. j. 2021; 13(2): 235-238